1976
DOI: 10.1073/pnas.73.7.2501
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between nutritional factors and drug biotransformations in man.

Abstract: This study was undertaken to examine the influence of nutritional factors on the activity of the mixed function oxidase system in man, which is cytochrome P450 dependent. Three normal volunteers were fed a low carbohydrate-high protein diet for 2 weeks, followed by a high carbohydrate-low protein diet for the following 2 weeks. At the end of each test diet period, the plasma elimination rates of antipyrine and theophylline were determined. The mean plasma half-life for antipyrine was 17.5 hr on the high carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Prooxidant states can be produced by radiation, hyperbaric oxygen, xenobiotic metabolites, Fenton-type reagents, 2). In our study, we found evidence (although indirect) that the amount of dietary lipids, known to be an enhancing factor in tumor development, can also modulate levels ofprooxidant states in the body.…”
Section: Discussionsupporting
confidence: 51%
“…Prooxidant states can be produced by radiation, hyperbaric oxygen, xenobiotic metabolites, Fenton-type reagents, 2). In our study, we found evidence (although indirect) that the amount of dietary lipids, known to be an enhancing factor in tumor development, can also modulate levels ofprooxidant states in the body.…”
Section: Discussionsupporting
confidence: 51%
“…Proof of a cause-and-effect relationship is more difficult and it is usually necessary to proceed to controlled studies in which single factors are examined in isolation, others being held constant. Alvares, Anderson, Conney & Kappas (1976) showed, using this technique, that high protein diets accelerated both antipyrine and theophylline elimination, and a similar approach will be necessary as other environmental factors, with a potential for altering drug clearance, are identified.…”
Section: Discussionmentioning
confidence: 99%
“…Potential sources of such variability could be environmental, pathophysiological or genetic (Alvares et al, 1976;Dollery et al, 1979;Vesell, 1973). Recent interest has focussed on the genetic regulation of cytochrome P450 mixed function oxidases (Alvan et al, 1990).…”
Section: Introductionmentioning
confidence: 99%